Driving Efficiency: Advancements in Garage Parking Assistance - ParkPal - Adnan K. Shaout; Asha Sikligar; Shikha Sikligar; Tidiane Diaby (Journal of Engineering Research and Reviews)
Aim/background: In this paper, we propose a solution to mitigate parking lot accidents by developing a garage parking sensor system.